Temperament and Psychological Well-Being in Emerging Adulthood: The Mediating Role of Perceived Social Support - Ato, Ester; Galián , María Dolores (Studia Psychologica, 2026)
The university period is a stage of life often associated with lower levels of psychological well-being and life satisfaction, highlighting the need to investigate factors contributing to this decline. This study aimed to examine the relationship between temperament and psychological well-being, and the potential mediating role of perceived social support, in a sample of Spanish university students (N = 332; M = 19.28). Participants completed a set of self-report instruments, including the Adult Temperament Questionnaire, the Multidimensional Scale of Perceived Social Support, and the Scales of Psychological Well-Being. Results showed that high levels of negative emotionality, and low levels of effortful control and surgency, significantly predicted poorer outcomes across multiple psychological well-being dimensions. Perceived social support, particularly from family and friends, also contributed significantly to higher well-being, more so than support from other significant individuals. Furthermore, complementary and indirect-only mediation effects of perceived social support were identified between temperament constructs and well-being dimensions. Overall, these findings enhance our understanding of the interplay between temperament, social support, and psychological well-being during emerging adulthood, within the Spanish cultural context.